Analysis of equilibrium and kinetic parameters of water adsorption heating systems for different porous metal/metalloid oxide adsorbents. (5th May 2016) - Pinheiro, Joana M.; Salústio, Sérgio; Rocha, João; Valente, Anabela A.; Silva, Carlos M.
Highlights: Modelled/simulated water AHSs using different porous metal/metalloid oxides. Zeolite 13X/water is the most promising pair with COP = 1.48 and S H P = 1232 W kg s − 1 . Good prediction of the performance of AHSs using constant λ eff, s, Q ads and K LDF . Performance of AHS not significantly influenced for d p up to 0.6 mm. Abstract: The performances of well-known porous metal/metalloid oxide adsorbents (zeolite 13X, zeolite 4A and silica gel) and less explored Engelhard titanosilicate ETS-10 for water adsorption heating systems (AHSs) were compared with the aid of computational modelling and simulations. The developed model contemplated adsorption equilibrium, one-dimensional heat and mass transfer in the bed, external heat transfer limitations, and intraparticle mass transport. The pair zeolite 13X/water seemed most promising for the AHS partly due to a higher amount of heat generated per cycle, and favourable water-adsorption isotherm features. Based on sensitivity studies, for zeolite particle diameters in the range 0.2–0.6 mm, the coefficient of performance was 1.48 and the specific heating power was in the range 1141–1254 W kgs −1 . Aiming at inferior computational and numerical efforts, the impact of considering some simplified postulations (e.g. constant thermal conductivity of the adsorbent; constant isosteric heat of adsorption; constant linear driving force coefficient), while ensuring comparable predictions of the performances of the AHSs, was successfully investigated.